Utilizing a Photo-Analysis Software for Content Identifying Method (CIM) - Nejad Nasim Sahraei; Ali Sharghi (Journal of Landscape Ecology, 2015)
Content Identifying Methodology or (CIM) was developed to measure public preferences in order to reveal the common characteristics of landscapes and aspects of underlying perceptions including the individual's reactions to content and spatial configuration, therefore, it can assist with the identification of factors that influenced preference. Regarding the analysis of landscape photographs through CIM, there are several studies utilizing image analysis software, such as Adobe Photoshop, in order to identify the physical contents in the scenes. This study attempts to evaluate public’s ‘preferences for aesthetic qualities of pedestrian bridges in urban areas through a photo-questionnaire survey, in which respondents evaluated images of pedestrian bridges in urban areas. Two groups of images were evaluated as the most and least preferred scenes that concern the highest and lowest mean scores respectively. These two groups were analyzed by CIM and also evaluated based on the respondent’s description of each group to reveal the pattern of preferences and the factors that may affect them. Digimizer Software was employed to triangulate the two approaches and to determine the role of these factors on people’s preferences. This study attempts to introduce the useful software for image analysis which can measure the physical contents and also their spatial organization in the scenes. According to the findings, it is revealed that Digimizer could be a useful tool in CIM approaches through preference studies that utilizes photographs in place of the actual landscape in order to determine the most important factors in public preferences for pedestrian bridges in urban areas.